Hylomecon japonica: A Review About Botanical Aspects, Traditional Applications, Chemical Composition, and Pharmacological Properties - Yue Tian; Guangqing Xia; Junyi Zhu; Li Li; Hao Zang (Horticulturae)
Hylomecon japonica (Thunb.) Prantl et Kundig is a plant whose root and rhizome belong to the genus Hylomecon within the Papaveraceae family. It has a long medicinal history and has been traditionally used to treat various conditions, including wind–cold–dampness obstruction syndrome, rheumatic joint pain, traumatic injuries, excessive fatigue, weakness of the limbs, epigastric pain, and dysentery. Modern pharmacological research confirms that Hylomecon japonica exhibits effects such as anticancer, anti-inflammatory, and antibacterial activities. To gain a comprehensive understanding of this plant, a thorough literature review was conducted using databases like Scifinder, Web of Science, PubMed, Scopus, and CNKI. This review provides an overview of the traditional applications, geographical distribution, botanical description, chemical composition, and pharmacological effects of Hylomecon japonica. Researchers have isolated and identified a total of one hundred and thirty-five components from Hylomecon japonica, including alkaloids, saponins, phenolics, flavonoids, other compounds, and trace elements. Notably, alkaloids and saponins have shown significant anti-tumor and antibacterial effects. Additionally, extracts of Hylomecon japonica have demonstrated promising activity in anti-inflammatory, anti-obesity, and varicose vein treatment applications. Despite the existing foundational research, further studies are necessary to enhance our understanding of its mechanisms and pathways of action. This research will provide valuable references for active ingredient research and the development and utilization of Hylomecon japonica’s medicinal value. By continuing to explore this plant’s potential, we can pave the way for new therapeutic advancements and improve health outcomes for patients worldwide.